OPINI MAHASISWA ILMU KOMUNIKASI TERHADAP FENOMENA CYBERSTALKING DI MEDIA SOSIAL - Yusaputra, Muhammad Isa; Sari, Dyah Fitria Kartika; Utama, Roman R.; Husnuzan, Aldina (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2018)
Cyberstalking behavior that leads to the attack of one's privacy area has not happened much in Indonesia but does not rule out the possibility of seeing the percentage of Indonesian people as internet users constantly increasing. This behavior can be compared to cyberbulliying but has more indications where the perpetrator continues to follow victims in cyberspace to sometimes in the real world. Seeing this problem, this study describes the opinions of students of communication science on cyberstalking behavior. By using uncertainty reduction theory through three approaches strategies, namely passive strategies, active strategies and interactive strategies associated with cyberstalking phenomena. Retrieval of data in this study uses a questionnaire with the presentation of quantitative data, where the results of data processing are described. Cyberstalking is an inevitable phenomenon of technological development, in a passive strategy in some cases recognizing the nature and behavior of someone from social media, is not an easy thing to do. Active strategies that involve communication with people around the target, can be done by searching for information through social media, although to recognize the nature and behavior of a person is not easy, but finding information about others on social media in the phenomenon of cyberstlaking is one of the steps interfere with the lives of others. The process that has involved direct interaction with victims is an interactive strategy that has been very disturbing to others. Cyberstalking which happens also lies behind many factors, it can be from yourself, others, even the surrounding environment.